Evaluation of ultrasound‐guided vascular access in dogs. (19th September 2013) - Chamberlin, Scott C.; Sullivan, Lauren A.; Morley, Paul S.; Boscan, Pedro
Abstract Objective To describe the technique and determine the feasibility, success rate, perceived difficulty, and time to vascular access using ultrasound guidance for jugular vein catheterization in a cardiac arrest dog model. Design Prospective descriptive study. Setting University teaching hospital. Animals Nine Walker hounds. Measurements and Main Results A total of 27 jugular catheterizations were performed postcardiac arrest using ultrasound guidance. Catheterizations were recorded based on the order in which they were performed and presence/absence of a hematoma around the vein. Time (minutes) until successful vascular access and perceived difficulty in achieving vascular access (scale of 1 = easy to 10 = difficult) were recorded for each catheterization. Mean time to vascular access was 1.9 minutes (95% confidence interval, 1.1–3.4 min) for catheterizations without hematoma, versus 4.3 minutes (1.8–10.1 min) for catheterizations with hematoma (P = 0.1). Median perceived difficulty was 2 of 10 (range 1–7) for catheterizations without hematoma, versus 2 of 10 (range 1–8) for catheterizations with hematoma (P = 0.3). A learning curve was evaluated by comparing mean time to vascular access and perceived difficulty in initial versus subsequent catheterizations. Mean time to vascular access was 2.5 minutes (1.0–6.4 min) in the initial 13 catheterizations versus 3.3 minutes (1.5–7.5 min) in the subsequent 14 catheterizations (P = 0.6). Median perceived difficulty in the first 13 catheterizations (3, range 1–8) was significantly greater (P = 0.049) than median perceived difficulty in the subsequent 14 catheterizations (2, range 1–6). Conclusions Ultrasound‐guided jugular catheterization is associated with a learning curve but is successful in obtaining rapid vascular access in dogs. Further prospective studies are warranted to confirm the utility of this technique in a clinical setting.